EFFECTIVENESS OF BIOMEDICAL MATRICULATION FACULTY OF MEDICINE (A QUALITATIVE STUDY) - Lepertery, Johan Weinand; Taihuttu, Yuniasih M.J.; Titaley, Christiana R. (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Changes in learning methods from teacher-centered to student-centered, in addition to the different subjects taught compared to the high school, could be challenging for new medical students. Biomedical matriculation is carried out for new students to equalize perceptions and knowledge before the first semester starts. This study explored student perceptions about the effectiveness of biomedical matriculation activities at the Faculty of Medicine, University of Pattimura, Ambon.Methods: This qualitative study was conducted with 20 students from the Faculty of Medicine, University of Pattimura who were in their first year of the 2022/2023 academic year. Data were collected using in-depth interviews.Results: The results showed that many students at the beginning of the intake needed to be made aware of biomedical matriculation. Consequently, this adversely impacts the informants' readiness to participate in the program. Students admitted that they began to adapt as the learning activities progressed in matriculation. The informants also agreed that biomedical matriculation was effective in helping them during their first year. It provided new knowledge regarding the subjects studied and helped them adapt to the learning methods of the faculty and in their preparation for class later.Conclusion: Most informants mentioned that the supporting components in biomedical matriculation, such as the material taught, lecturers as well as infrastructure also supported them in their adaption to the new academic life at the faculty.